Pelatihan Penulisan Laporan Litmas Di Bapas Kelas 1 Banjarmasin - Jamiatul Hamidah; Akhmad Syakir; Sri Normuliati; Istiqamah Istiqamah (LPPM UMRI, 2020)
Bapas plays a role in mentoring clients and one of his duties is to make community research reports (Litmas). Considering the importance and importance of Litmas in helping judges to make a right and fair decision, to determine appropriate coaching therapy, the Litmas report must be able to provide a clear picture of the background of the client's life, both in the past and after becoming a client. All problems contained in life and the social environment are covered in the Litmas content report. The purpose of this activity is to: (1) Improve the ability to write scientific papers of PK. (2) Improve understanding of Indonesian spelling rules. (3) Provide training in writing narrative from interviews and observations. The activity was carried out for one day which was divided into 3 sessions. From the results of the activity, it was concluded that many Litmas writing violated the rules of the General Guidelines for Indonesian Spelling. In addition, the obstacle faced by PK in writing Litmas is the difficulty in transforming the data obtained in the field into narrative form.